2018
DOI: 10.1017/neu.2018.30
|View full text |Cite
|
Sign up to set email alerts
|

Relapse of drunk driving and association with traffic accidents, alcohol-related problems and biomarkers of impulsivity

Abstract: ObjectiveIndividual biological predispositions should play a role in risky driving behaviour. Platelet monoamine oxidase (MAO) activity, dopamine transporter gene (DAT1) and neuropeptide S receptor 1 (NPSR1) gene polymorphisms have been identified as markers of impulsivity, alcohol use and excessive risk-taking. We aimed to find out how this knowledge on neurobiology of impulsivity applies to drunk driving and traffic behaviour in general.MethodsWe have longitudinally examined the behaviour of drunk drivers (n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

5
3

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 53 publications
2
3
0
Order By: Relevance
“…We did not observe any surplus of 9R in the ADHD screener positives, but the genotype together with positive screener presented an additive effect to traffic risk. This seems also in line with our previous smaller study on a different sample where 9R carriers had more accidents in traffic through their own fault (Tokko et al, 2019). It might be that the drivers with self-reported ADHD symptoms and the risk-allele of the dopamine transporter gene are more prone to traffic offences and/or collisions.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…We did not observe any surplus of 9R in the ADHD screener positives, but the genotype together with positive screener presented an additive effect to traffic risk. This seems also in line with our previous smaller study on a different sample where 9R carriers had more accidents in traffic through their own fault (Tokko et al, 2019). It might be that the drivers with self-reported ADHD symptoms and the risk-allele of the dopamine transporter gene are more prone to traffic offences and/or collisions.…”
Section: Discussionsupporting
confidence: 90%
“…Being a 9R carrier has been associated with persistent ADHD in adults (Franke et al, 2012(Franke et al, , 2010. This genotype can also be associated with traffic risks: We have previously found that male 9R carriers had more accidents in traffic by their own fault (Tokko et al, 2019) and, in another sample, a higher general traffic risk (Luht et al, 2019).…”
Section: Introductionmentioning
confidence: 94%
“…Among males the proportion of DAT1 VNTR 9R carriers was higher among drunk drivers and subjects with high general traffic risk. These results support the significant role of dopaminergic system in impulse control and risk-taking behaviour (3741) and the potentially higher risk in DAT1 VNTR 9R allele carriers (45,46,60), including in traffic (61). In females, carrier status of the DAT1 VNTR 9R allele had no significant association with traffic behaviour at baseline, but prevented the intervention effect to occur.…”
Section: Discussionsupporting
confidence: 75%
“…Low serum lipid levels have repeatedly been linked to several psychopathologies, including violent criminal behaviour (Repo-Tiihonen et al, 2002), aggression towards others and self (Sahebzamani et al, 2013) and suicide (Daray et al, 2018). Impulsivity, being an essential feature of disruptive behaviour disorders (Dougherty et al, 1999), excessive risk taking (Eensoo et al, 2018;Tokko et al, 2019) and pathologically aggressive (Barratt et al, 1999) or suicidal behaviour (Corruble et al, 1999), is one of the key elements of maladaptive behaviours associated with low cholesterol levels (Troisi, 2011). However, results of some studies have been in conflict with the assumption that cholesterol levels and impulsivity, aggressiveness or suicidality could be correlated in a general and linear manner (Corruble et al, 1999;Troisi, 2011;Tomson-Johanson and Harro, 2018).…”
Section: Introductionmentioning
confidence: 99%